Multidimensional scaling (MDS) to visual representation of proximities for quality and phytochemical characteristics in Vitis vinifera L. cv. ‘Erciş’ - Keskin, Nurhan (Progress in Nutrition, 2017)
This study was conducted to determine quality and phytochemical characteristics of ‘Ercis’ cultivar that is indigenous to Van province for wine and must as well as table grapes due to specific aroma. In this framework, physical (color, cluster weight (g), berry length (mm), berry width (mm) and berry weight (g)), chemical (pH, titratable acidity (TA%), total soluble solids (TSS%), maturation index (MI), sugars, organic acids, total antioxidant activity, macro and micro elements) and phytochemical characteristics (phenolic compounds) of the cultivar were examined.  Paired sample t test was performed to determine differences between years. In addition, multidimensional scaling was utilized to indicate visual representation of proximities for the characteristics. Differences between years for cluster weight, berry length, berry width and berry weight were found statistically significant, however, there is no significant differences for other characteristics. In addition, some negative and positive correlations were observed among the physical, chemical and phytochemical characteristics.